2018
DOI: 10.3390/metabo8040075
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography Mass Spectrometry (GC-MS) Quantification of Metabolites in Stool Using 13C Labelled Compounds

Abstract: It has become increasingly important to qualitatively and quantitatively assess the volatile metabolites in a range of bodily fluids for use in monitoring health. There has been relatively little work on the quantitative analysis of compounds, particularly with respect to the effects of ethnicity or geographic location. A novel method for the quantification of compounds in stool using 13C labelled compounds as internal standards is presented. Using thermal desorption gas chromatography mass spectrometry, stool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This study is unique as it is the only work we have identified in which many compounds were quantified based on what is in the faeces and not just the headspace. This work also turned the faeces alkaline by the addition of sodium hydroxide to quantify trimethylamine, which is the first-time this has been reported from faeces [216]. This paper contributed 12 new compounds to the previous compendium [1], including 4-isopropyl benzaldehyde (cuminaldehyde), and 2, 4-dithiapentane which are associated with cumin and truffle fungus, respectively.…”
Section: Volatile Organic Compounds From Faecesmentioning
confidence: 91%
See 1 more Smart Citation
“…This study is unique as it is the only work we have identified in which many compounds were quantified based on what is in the faeces and not just the headspace. This work also turned the faeces alkaline by the addition of sodium hydroxide to quantify trimethylamine, which is the first-time this has been reported from faeces [216]. This paper contributed 12 new compounds to the previous compendium [1], including 4-isopropyl benzaldehyde (cuminaldehyde), and 2, 4-dithiapentane which are associated with cumin and truffle fungus, respectively.…”
Section: Volatile Organic Compounds From Faecesmentioning
confidence: 91%
“…Gould et al [216], conducted a study in which 13 C labelled compounds were used as internal standards in faecal samples to quantify 15 compounds. This study is unique as it is the only work we have identified in which many compounds were quantified based on what is in the faeces and not just the headspace.…”
Section: Volatile Organic Compounds From Faecesmentioning
confidence: 99%
“…Ethyl 2-methylbutyrate, as a kind of fatty acid ethyl ester (FAEE), has been detected in VOCs of breath, feces, and cells. , FAEEs are nonoxidative ethanol metabolites that have been implicated as mediators of ethanol-induced cell injury and associated with pancreatic cancer . Silva et al utilized the GC–MS technique and reported higher levels of ethyl 2-methylbutyrate in the headspace of breast cancer cells compared to normal human mammary epithelial cells .…”
Section: Discussionmentioning
confidence: 99%